Inventarisasi Tanaman Bernilai Ekonomi Sebagai Obat Tradisional Suku Bugis di Kabupaten Bone Sulawesi Selatan - Syamsuri Syamsuri; Muh. Sri Yusal; Hasria Alang (Program of Biology Education, Universitas Lambung Mangkurat, 2023)
Ethnoeconomics is a branch of ethnobotany that studies the role of plants that have economic value, one of which is as traditional medicine by an ethnic group or ethnomedicine. The purpose of this study was to inventory traditional medicinal plants of the Bugis tribe in South Sulawesi as ethnomedicines. The research was conducted from November 2022 to January 2023 in Pallae Village, Cenrana District, Bone Regency, South Sulawesi. This type of the research was qualitative descriptive, to describe the use of plants as traditional medicine. Data collection techniques through interviews, observation, and literature studies. Respondents were selected by purposive sampling. Research data were analyzed descriptively and compared with scientific data or scientific data. Based on the results of the study, the types of plants used as traditional medicine by the Bugis tribe in the research location were noni, belimbing wuluh, sidaguri, areca nut, moringa, broken glass, cat's whiskers, ginger, bangle, turmeric, lemongrass, aloe vera, betel, tobacco, soursop and bagore. Plant organs used as medicine are fruit, leaves, rhizomes, and mucus